(untitled) (World Bulletin of Social Sciences, 2025)
The rapid development of information technology (IT) has significantly transformed the field of education, including the teaching and learning of English. This article explores the role of IT in English language teaching, highlighting its benefits, applications, and challenges. Digital tools such as online platforms, multimedia resources, and artificial intelligence – based applications have enhanced learner engagement, improved access to authentic materials, and supported personalized learning. At the same time, the integration of IT requires careful pedagogical planning, teacher training, and consideration of accessibility. The article concludes that IT, when used effectively, can greatly improve English language education.